2022
DOI: 10.3389/fgene.2022.877174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ABCA1 and FNDC3B Gene Polymorphisms Associated With Pseudoexfoliation Glaucoma and Primary Angle-Closure Glaucoma in a Saudi Cohort

Abstract: Objective: It is plausible that common disease mechanisms exist in glaucoma pathophysiology. Accordingly, we investigated the genetic association of two previously reported primary open-angle glaucoma (POAG)-related gene polymorphisms, rs2472493 (A > G) in ABCA1 and rs7636836 (C > T) in FNDC3B, in primary angle-closure glaucoma (PACG) and pseudoexfoliation glaucoma (PXG).Methods: TaqMan genotyping was performed in a total of 442 subjects consisting of 246 healthy controls, 102 PACG patients, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…By contrast, another large multi-ethnic meta-analysis reported a negative association ( 138 ). Studies in Brazilian, Afroamerican, Chinese, and Arab populations failed to detect any association between this Abca1 polymorphism and different types of glaucoma ( 132 , 133 , 136 , 140 , 141 ). Interestingly, it was recently shown that this rs2472493 genetic variant attenuates Abca1 expression in a model of cultured cells using a luciferase reporter gene under the control of a human Abca1 promoter harboring the POAG risk allele [G] ( 66 ).…”
Section: Cholesterol Oxysterols and Glaucomamentioning
confidence: 91%
“…By contrast, another large multi-ethnic meta-analysis reported a negative association ( 138 ). Studies in Brazilian, Afroamerican, Chinese, and Arab populations failed to detect any association between this Abca1 polymorphism and different types of glaucoma ( 132 , 133 , 136 , 140 , 141 ). Interestingly, it was recently shown that this rs2472493 genetic variant attenuates Abca1 expression in a model of cultured cells using a luciferase reporter gene under the control of a human Abca1 promoter harboring the POAG risk allele [G] ( 66 ).…”
Section: Cholesterol Oxysterols and Glaucomamentioning
confidence: 91%
“…DNA extracted from EDTA blood were genotyped for the rs2472493 (A > G), rs7636836 (C > T), and rs61275591 (G > A) polymorphisms using commercially available TaqMan ® assays, C__16235609_10, C_189412462_10, and C__88653935_10 (catalog number: 4351379; Applied Biosystems Inc., Foster City, CA, USA) on ABI-7500 real-time PCR (Applied Biosystems) as recommended by the manufacturer and described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a retrospective and exploratory case-control study, sanctioned by the Institutional Review Board Ethics Committee at the College of Medicine of King Saud University as per the principles of the Declaration of Helsinki guidelines for human research. Participants were recruited at King Abdulaziz University Hospital in Riyadh, Saudi Arabia, as described elsewhere [58].…”
Section: Study Design Ethics Approval and Participant Characteristicsmentioning
confidence: 99%